The Production And Characterization Of Near Stoichiometric NdFeB-Type HDDR Powder - Shaaban, Azizah (2007)
A study of the processing of HDDR powder with the composition Nd12.7FesuB6.o and Nd12.2Fe81.2B5.9Zr0.1 have been undertaken. The homogenized alloys were disproportionated at 850°C for 30 minutes and employing a range of recombination temperatures from 790°C to 920°C. The optimum recombination temperature in the HDDR treatment was found to be 880°C. Zr-addition appears to inhibit grain growth during the treatment process.